Elaboración y aplicación de un manual de estratégias metodológicas de expresión corporal para desarrollar la inteligencia espacial en los niños de 3 a 4 años del centro infantil “mi pequeño mundo” del cantón pujilí barrio bellavista en el año lectivo 2012- 2013 - Cárdenas Pila, Victoria Nataly (2014)
This research contribution contains important ways to improve the teachinglearning process by strengthening the spatial intelligence of children of 3-4 years through body language. After detecting the problem that arose in children, as the acquisition of new knowledge, formulating clear, measurable and achievable goals. It is supported by theoretical - practical way, through important aspects that allowed the development of a methodological manual body language strategy to develop spatial intelligence in children. Man can know the outside world in various ways of intelligence by exploiting through movement in body psychomotor game. Through the different movements of personal and creative way possible by constituting a language be developed in different methodological strategies such as play, dance, drama and children's gymnastics Keywords: Body Language, psychomotor, Multiple